Have economists actually solved the WTO trade effects mystery? - Wei, Changyou (Kansas State University, 2012)
Rose (2004) reports that GATT/WTO membership produces no positive effects on international trade. This is a remarkable determination given the widespread belief in academic and policy circles that the WTO successfully promotes trade flows by reducing barriers to international trade. Empirical literature measuring the GATT/WTO trade effects has produced notably diverse results since Rose's (2004) paper. This report introduces the history of GATT/WTO and describes the GATT/WTO’s aim to promote trade using multilateral rounds of trade negotiations. It confirms that the efforts toward trade liberalization made by the GATT/WTO are partially achieved by tariff reductions and other trade obligations. In discussing the literature related to Rose’s surprising results, we argue that the gravity model employed by Rose (2004) is not theoretically sound since it omits multilateral resistance terms and fails to capture unobserved bilateral heterogeneity. However, we find that even an accurate specification gravity model that controls multilateral resistance, unobserved bilateral heterogeneity, and individual regional trade agreement effect cannot fully account for Rose’s GATT/WTO trade effects findings. The present report suggests that a new approach, specifically the nonparametric method used by Chang and Lee (2011), may offer sound guidance for future research attempting to understand Rose’s mysterious findings.
Keywords: GATT/WTO; Gravity model; Trade effect; Economics (0501)